Development of Integrated Thematic Teaching Materials with Mind Mapping Model in Class III of Elementary School - Delfakhria Delfakhria; Solfema Solfema (STAI Hubbulwathan Duri, 2022)
The research aims to produce an integrated thematic lesson material in class III with a valid, practical, and effective mind mapping model. The research carried out is in the type of 4D model development research. The definition stage consists of needs analysis and student analysis. The design stage consists of designing lesson plans and teaching materials. The lesson plans and valid teaching materials are tested on third-grade students of SD Negeri 54 Anak Air Kec. Koto Tangah, Padang, Semester 1 with 1 observer. Collecting data in the study using a 5-scale questionnaire to determine the level of validity, practicality, and student learning motivation as well as pre-test and post-test in the form of objective questions to see the achievement of student learning outcomes. The validation of teaching materials from the media aspect is 82%, the material aspects of RPP validation are 92%, the validation of teaching materials is 95%, and the language aspect is 98%. The results of the teacher's questionnaire are efficient, 92% are efficient, the average student questionnaire results are 88 very practical, and the results of the effectiveness experiment on increasing students' learning motivation are 83% in the very practical category. Thus, the development of learning materials with a mind map model assisted by Google Slides in grade III Elementary School is categorized as valid, practical, and effective.